Sustainable shipping strategies of liner companies in this economic downturn - Boey, Yi Heen (2017)
The liner shipping industry has been plagued by low demand and an ongoing supply glut. Liner shipping companies have found it increasingly hard to stay afloat due to falling profit margins and most of the time, they are just trying to cut losses. The purpose of this study is to understand how liner shipping companies can increase economic sustainability during a downturn. Despite to the largely similar service offered and transparency of the freight market, blindly adopting a cost-leadership model is unsustainable, this is made clear when a price war caused freight rates to plummet. Moreover, customers do not make decisions based on price alone. There are many other differentiating factors can come into play when customers decide which carrier to use, a more comprehensive metric would be customer satisfaction in service quality. This paper posits that a systematic way of mapping out customer requirements and quality characteristics will allow liner shipping companies to determine which are the most efficient and effective business strategies in increasing customer satisfaction during the economic downturn. It is only by making sure that customer requirements and opinions are a factor input that we can be sure that Business Strategies recommended can fully address customer expectations of a shipping service. The research process uses a 2-phase House of Quality, a hybrid version of Quality Functional Deployment to achieve this. The 2-phase House of Quality allows the use of quality characteristics as a link between customer requirements and business strategies. Customers (Freight Forwarders) and Liner shipping companies were surveyed extensively to generate scores for the House of Quality. Interviews were also conducted with senior management from Liner Shipping companies to ensure that any anomalies or trends were properly addressed. The results of House of Quality process was that mergers and acquisitions was the most effective and efficient business strategy in an economic downturn. Other business strategies in the top 3 were increasing collaboration with ports & terminals and also forming alliances. On the other hand, the strategy of scrapping ships ranked the lowest out of the nine strategies being assessed. This could be due to the fact that business & restructuring strategy usually requires less capital and resources, logically entailing lesser risks. While business and restructuring strategies are generally popular and effective in allowing companies to increasing economic sustainability through maximizing customer satisfaction but there are other options should regulators or investors decide to intervene in the strategizing process.